Application of Google Classroom in promoting independent learning of non-English major students in English class in a police institution - Nguyễn, Duy Quynh (2020)
This study was expected to investigate the application of Google Classroom to promote the independent learning of non-English major students studying in a police institution. More explicitly, the author attempted to carry out his intervention throughout one cyclical process of action research and targeted at examining 1) impacts of the application of Google Classroom on the students’ independent learning in their English class and 2) the students’ opinions towards the application of Google Classroom in their English learning. The data were collected from pre-intervention and post-intervention questionnaires delivered to the participants, and interviews with some of the students. The time span of the intervention was 14 weeks in total and all findings indicated in the study were interpreted as the result of one-cycle implementation of the action research project. It was concluded that the application of Google Classroom was beneficial to the majority of the students and their independent learning was positively influenced. The primary evidence was found in improvement of the students in terms of English task completion and their increasingly positive feeling and motivation. From the findings of the research, it is suggested that adapting a new approach in English language teaching should be considered in the context of the police institution.